(untitled) (The Pakistan Development Review, 1998)
Land and irrigation are the basic resources in agriculture. The role and importance of these resources and their contribution towards productivity, in the context of the country’s increasing population, can hardly be exaggerated. Pakistani agriculture is set in a very distinctive situation of an increasing population on the one hand and diminishing resources on the other. The population of Pakistan was reported to be 131.63 million in 1996 and is projected to be 207 million in 2013 [Pakistan (1996) and WSIP (1990)]. The agriculture sector has to face the difficult task of doubling the existing food production by the turn of this century. The situation demands horizontal and vertical growth in the productivity, either by bringing more land under cultivation, or by increasing the cropping intensity of the existing land resources. This can also be accomplished by bringing more land under cultivation from the cultivable uncultivated area (a large proportion of which exists on medium and large farms under waterlogged or saline conditions). In this context, it becomes important to identify the nature of the relationship that exists between farm size and unculturable wastelands and the kinds of changes the green revolution/SCARPs projects introduced to this relationship.